Food Safety Practices Among Street Food Vendors In The Twin Cities Of Zamboanga Del Norte - Solon, Jan Jacob C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This paper aimed to examine the food safety practices among street food vendors in the Twin Cities of Zamboanga del Norte. Food safety practices covered two indicators; Sanitation and Personal Hygiene practices. There were two types of respondents in the study. First, there were 50 owners and proprietors of street food vendors in the twin cities, breakdown into 25 respondents for each City. Second, there were 400 total respondents in the study, and these were customers of the street food vendors; 200 respondents were allocated for Dapitan, while another 200 respondents were from Dipolog City. The study revealed that the majority of street vendor owners are college graduates. However, 98% or 49 of the respondents have not attended any food safety seminars. Further, sanitation practices are often practiced. Moreover, personal hygiene practices were frequently and sometimes practiced. There was a significant difference in the personal hygiene practices of when group according to Age. It implies that the younger generation of street vendors are still learning and could eventually learn as they grow older. A strong reason why hygiene practices differ between young and old street food vendors in these two cities. Most street vendors are mature individuals but are still active in the street vending business. However, these street food vendors still have poor food safety practices for a lack of appropriate knowledge, and most did not attend any sanitation and personal hygiene seminars/ workshops. Street vendors may be subject to a regular sanitary inspection regarding how street food merchants sell their goods to prevent contamination and keep the food they serve from any health risks. The LGU of both Cities may organize a seminar/training related to sanitation and personal hygiene to improve the standard of their Food vending continuously. A policy/program to be developed by each LGU as their support for these street food vendors.